ANALISIS SISTEM PAKAR DIAGNOSA HAMA DAN PENYAKIT PADA TANAMAN PINANG MENGGUNAKAN METODE FORWARD CHAINNING - Rosmaneli, Rosmaneli (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2020)
The presentation of information is growing rapidly over time. Starting from text, voice, images and videos. It continues to grow and is influenced by improvements in information presentation technology. The computers as an information technology are often used as human intermediaries for an information system. This is evidenced by the emergence of various systems related to computers as data processing. One application is the Expert System.